Dokumentiranje testnih vzorcev - Dogša, Tomaž (Uporabna informatika (Ljubljana), 1999)
One of the most important elements in testing process are test cases. They areso important because a lot of effort is spent on test case design. In this paper the characteristics of test will be described together with the most important attributes and organisation of test data, as well as other particularities.
Keywords: ponovljivost; programska oprema; testiranje; testni vzorci